Determinan Sosio-Demografi Pendapatan Penduduk Bekerja Di Kawasan Pinggiran Kota - Oktalia, Hening Januar; Giyarsih, Sri Rum; Budiani, Sri Rahayu; Marwasta, Djaka (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Abstract. Provinsi Daerah Istimewa Yogyakarta has a high quality of human resources. The relatively good quality of human resources, especially in Kabupaten Sleman, should be accompanied by a relatively high level of labor income. The quality of human development in this province ranks top nationally, but the wages/income of the working population in this province are still relatively low. This study uses primary data obtained by interviewing all residents in one of the areas in Tambak Bayan, Catur Tunggal, Depok, Sleman. This area is classified as a fairly elite area, but the working population in this area does not all have incomes that are included in the high category. The working population in this area is still dominated by residents with low and medium income levels. The purpose of this study is to determine the description of the socio-demographic characteristics and income of the working population in the area and to identify the influence of socio-demographic variables on workers' income. The analysis method used was descriptive analysis with cross tabulation and chi-square test. The findings of this study include the relationship between the variables of education, training and working hours to workers' income. Keyword: sociodemographic, wage, working population